Clinical Steps for Restoration of Fractured Anterior Teeth: Color Protocol with Non-VITA Scale. (28th May 2019) - Gaião, Ubiracy; da Cunha, Leonardo Fernandes; de Almeida Kintopp, Cibele; Garcia, André Vivan; Gonzaga, Carla Castiglia; Moro, Alexandre; Correr, Gisele Maria
Abstract : Direct composite resin restorations are commonly provided because of their satisfactory esthetics and minimal wear of opposing tooth structure. Recent restorative systems may not follow the nomenclature of the classical VITA shade guide, using instead a simplified resin color system. A better understanding of these systems and their behavior regarding the incidence of light is an excellent approach to anterior restorations, especially for fractured anterior teeth. This paper demonstrates the color selection and clinical sequence for the natural reproduction of tooth structure using a resin system that does not follow the VITA classical scale.